UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VII-A SMPN 4 MADIUN MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) - Magdalena Yovita; Rudi Santoso Yohanes (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2016)
This research is aimed to increase critically thinking ability of the seven-year-students (class A) of SMP Negeri 4 Madiun through the application of Problem-Based Instruction Model. It is a classroom action research with two cycles. The subject of the study is the seven-year-students (class A) of SMP Negeri 4 Madiun in the academic year 2015-2016. The number of the subject is 30 students. The results of the research show that the average score for instructional activity is 2.66 in cicle (1), which is categorized as good and 3.48 in cicle (2) which is categorized as very good. It means that the researcher’s ability in the application of  Problem-Based Instruction Model is increasing and already reaches the determined success indicator. While, the critically thinking ability ofthe students is not increasing yet with average score 37.9 in cicle (1) and 75.69 in cicle (2). Further, the percentage of the class completion is 17.39 in cilce (1) and 56.52 in cilcle (2). It indicates that the students’ average score in the test  and the percentage of the completion are increasing, but do not yet reach the determined criteria. The Problem-Based Instruction Model is capable of increasing the critically thinking ability of the students; however, the increase is not optimum. Key words: critically thinking ability, Problem-Based Instruction Model